Legal Grounds For Artificial Intelligence Use In Law Enforcement: International And Foreign Experience - Kaliuzhnyi, Dmytro (Archives of Criminology and Forensic Sciences, 2024)
Artificial intelligence (AI) has become an integral part of modern law enforcement officers, providing them with unprecedented capabilities in crime prevention, investigation and analysis. AI technologies, such as biometrics and facial recognition systems, police activity forecasting algorithms, and AI-assisted X-ray interpretation, are transforming traditional methods of law enforcement officers’ work in order to increase their efficiency and effectiveness. However, along with potential advantages, the widespread adoption of AI in law enforcement raises ethical, legal, and social issues necessitating increased focus from government legislative, executive, and human rights authorities. The Article Purpose is to study regulatory and legal grounds for state regulation of AI technologies use in human rights protection activities in developed countries. Relying on the analysis of international and foreign experience, identify directions for further development of a corresponding Ukrainian legislation. Methodology: The main methodological approach applied is a regulatory approach. The paper will be based on the qualitative method consisting in the collection and processing of data to compare and interpret provisions or policies that support the implementation of AI in public life with adherence to the fundamental rights and freedoms, as well as ensuring safety and non-discrimination guarantees. The following methods have been applied in this article: research method, descriptive method, comparative and analytical method, interpretive analysis method, and illustrative method. Conclusions. Based on the analysis of regulations and legislative experience of the EU, the USA, and other developed countries involved in legal regulation of AI application, the author reveals trends and principles of AI technologies use in law enforcement. Namely: 1. Absolute majority of acts are aimed at protecting fundamental human rights and overall democratic functioning of society. 2. The principles of accountability, transparency and justice are found in nearly all well-known and common AI governance structures. 3. Singling out different forms of artificial intelligence. Most legal regulations distinguish between different types of AI systems depending on the risks they pose, the context in which they are used, or the specific type of system they create.